2012
DOI: 10.1186/ar3782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy on serum cytokines in SLE patients

Abstract: IntroductionThe aim of this study was to evaluate an extensive panel of cytokines involved in immune regulation during pregnancy in patients with systemic lupus erythematosus (SLE) and in healthy women.MethodsA total of 47 consecutive successful pregnancies in 46 SLE patients and 56 pregnancies in 56 matched healthy subjects, as controls, were prospectively studied. Serum interleukin (IL)-1-α, IL-1-β, IL-2, IL-6, IL-8, IL-10, IL-12p70, interferon (INF)-γ and tumor necrosis factor (TNF)-α were detected in sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Normal pregnancy is associated with hormonal, microbial and immunological changes, which prepare the maternal body for successful childbirth. Interestingly, some autoimmune diseases, including rheumatoid arthritis and multiple sclerosis, show improvement during pregnancy, while risk of flares increases postpartum 14–16. This suggests that pregnancy-induced physiological changes affect immune processes at peripheral sites, and it has been suggested that increased levels of Tregs and a shift towards Th2 cytokine patterns contribute to amelioration of Th1-driven diseases41 42 and conversely also play a role in exacerbation of Th2-driven inflammatory diseases such as systemic lupus erythematosus during pregnancy 43 44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal pregnancy is associated with hormonal, microbial and immunological changes, which prepare the maternal body for successful childbirth. Interestingly, some autoimmune diseases, including rheumatoid arthritis and multiple sclerosis, show improvement during pregnancy, while risk of flares increases postpartum 14–16. This suggests that pregnancy-induced physiological changes affect immune processes at peripheral sites, and it has been suggested that increased levels of Tregs and a shift towards Th2 cytokine patterns contribute to amelioration of Th1-driven diseases41 42 and conversely also play a role in exacerbation of Th2-driven inflammatory diseases such as systemic lupus erythematosus during pregnancy 43 44.…”
Section: Discussionmentioning
confidence: 99%
“…Successful implantation requires a proinflammatory Th1 environment at the maternal–fetal interface, which is followed by a shift towards a more tolerogenic Th2 response for the main duration of pregnancy, with again increased polarisation to a Th1 response shortly before partition 14 15. However, it is unclear to what extent placental immunological shifts actually translate to systemic immunological changes capable of affecting disease activity in the intestinal tract, as surprisingly few studies have investigated peripheral changes across the different trimesters of pregnancy, and those that did show conflicting results 16–18…”
Section: Introductionmentioning
confidence: 99%
“…Successful pregnancy has previously been described as predominantly a type 2 immune response-biased phenomenon [ 34 36 ]. In light of the collective evidence, it seems that the description of pregnancy in terms of type 2 immune responses may be oversimplified, both in the overall description of key cytokines/growth factors as well as in the temporal dynamics, and it is in need of further refinement.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the endocrine-immune interactions clearly play their fundamental role in pregnancy [34].…”
Section: • Rheumatoid Arthritismentioning
confidence: 99%